A Pathway Towards Net-Zero Emissions in Oil Refineries - Sunny, Nixon; Bernardi, Andrea; Danaci, David; Bui, Mai; Gonzalez-Garay, Andres; Chachuat, Benoît (Frontiers in Chemical Engineering, 2022)
Rapid industrialization and urbanization have increased the demand for both energy and mobility services across the globe, with accompanying increases in greenhouse gas emissions. This short paper analyzes strategic measures for the abatement of CO2 emissions from oil refinery operations. A case study involving a large conversion refinery shows that the use of post-combustion carbon capture and storage (CCS) may only be practical for large combined emission point sources, leaving about 30% of site-wide emissions unaddressed. A combination of post-combustion CCS with a CO2 capture rate well above 90% and other mitigation measures such as fuel substitution and emission offsets is needed to transition towards carbon-neutral refinery operations. All of these technologies must be configured to minimize environmental burden shifting and scope 2 emissions, whilst doing so cost-effectively to improve energy access and affordability. In the long run, scope 3 emissions from the combustion of refinery products and flaring must also be addressed. The use of synthetic fuels and alternative feedstocks such as liquefied plastic waste, instead of crude oil, could present a growth opportunity in a circular carbon economy.